The Royal Society, International Travel Grant Award - Keivanidis, Panagiotis E. (My University, 2026)
Principle Investigator in the Royal Society, International Travel Grant Award (2009R3), for the proposal ‘Monitoring the Charge Carrier Recombination Events in Organic Donor - Acceptor Photovoltaic Blends by Delayed Luminescence Spectroscopy’ (reference TG091471). Bilateral project between Imperial College London (UK) and Max Planck Institute for Polymer Research (DE)
Keywords: Natural sciences